2015
DOI: 10.1080/15321819.2015.1032305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bovine Viral Diarrhea Virus Envelope Glycoprotein E2 in YeastPichia pastorisand its Application to an ELISA for Detection of BVDV Neutralizing Antibodies in Cattle

Abstract: The aim of this article is to express envelope glycoprotein E2 of bovine viral diarrhea virus (BVDV) in yeast Pichia pastoris and its utility as a diagnostic antigen in ELISA. The BVDV E2 gene was cloned into the pPICZαA vector followed by integration into the Pichia pastoris strain X-33 genome for methanol-induced expression. SDS-PAGE and Western blot results showed that the recombinant BVDV E2 protein (72 kDa) was expressed and secreted into the medium at a concentration of 40 mg/L of culture under optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Various systems are currently available for exogenous gene expression, including E. coli expression systems, mammalian expression systems (Thomas et al 2009), Drosophila melanogaster systems (Robiolo and Schauer 2007), baculovirus expression systems (Pecora et al 2012;Zoth and Taboga 2006), Saccharomyces cerevisiae yeast systems (Patterson et al 2012), alfalfa plants (Aguirreburualde et al 2013), yeast Pichia pastoris expression systems (Behera et al 2015) and insect cell expression systems. However, the E. coli expression system remains the preferred choice for expressing foreign proteins due to its well-defined genetic background, rapid reproduction, cost-effectiveness, high expression levels, and ease of operation (Lee and Lee 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Various systems are currently available for exogenous gene expression, including E. coli expression systems, mammalian expression systems (Thomas et al 2009), Drosophila melanogaster systems (Robiolo and Schauer 2007), baculovirus expression systems (Pecora et al 2012;Zoth and Taboga 2006), Saccharomyces cerevisiae yeast systems (Patterson et al 2012), alfalfa plants (Aguirreburualde et al 2013), yeast Pichia pastoris expression systems (Behera et al 2015) and insect cell expression systems. However, the E. coli expression system remains the preferred choice for expressing foreign proteins due to its well-defined genetic background, rapid reproduction, cost-effectiveness, high expression levels, and ease of operation (Lee and Lee 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an indirect ELISA for specific detection of antibodies against CSFV based on the truncated E2 of CSFV (containing amino acids 690—879 in E2) expressed in mammalian cells has been reported, which did not cross-react serologically with anti-BVDV sera [ 17 ]. Previous reports demonstrated that the CSFV and BVDV proteins prepared from both prokaryotic and eukaryotic expression systems were used as the antigens for diagnostic ELISAs [ 8 , 17 , 34 , 39 ]. Although the biological activities of E rns and E2 glycoproteins expressed in E. coli may not be justifiable in the absence of post-translational modification, its use in the diagnostics may have the advantage of being economic, productive and fast.…”
Section: Discussionmentioning
confidence: 99%
“…Several well-known serological techniques, including immunofluorescence [9] and enzyme-linked immunosorbent assay (ELISA) [10], have been tested to potentially replace the neutralization test for other viruses. Recent studies have shown that rabies virus and bovine viral diarrhea virus glycoprotein serology ELISAs can measure the titers of neutralizing antibodies in sera from vaccinated humans and cattle, respectively [11,12]. The correlation of antibody titers between indirect ELISA and neutralization tests has also been studied in Zika virus and human papillomavirus [13,14].…”
Section: Introductionmentioning
confidence: 99%